(untitled) (Medicine Today, 2013)
A cross-sectional study was conducted in the department of Obstetrics & Gynaecology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka to determine the changes in serum lipid in 1st trimester of pregnancy over a period I year. A total of 91 subjects (60 women at first trimester of pregnancy assigned to case and 31 nonpregnant women with regular menstruation assigned to control) were included in the study. The mean age was significantly higher in control group than in case group (27.0± 4.3vs 24.4± 3.6 years respectively, p = 0.002). Lower socioeconomic class was predominance in case group (58.3%) and middle class (53.7%) in control group. The mean systolic and diastolic blood pressure was significantly higher in case group compared to control group. About 12% of patients had low HDL compared to 4.9% of controls (p=0.240). Raised LDL and raised triglycerides were found in 3.3% and 5% of the cases respectively while none of the control group had raised LDL and triglyceride (p = 0.350 and p = 0.25 respectively). The systolic and diastolic blood pressure was positively correlated with total cholesterol and HDL. However, LDL and triglyceride exhibit negative linear relationship in the both systolic and diastolic blood pressure. From this study, it can be concluded that pregnant mothers in their trimester had slightly altered serum lipids compared to their nonpregnant counterpart. DOI: http://dx.doi.org/10.3329/medtoday.v25i1.16065 Medicine Today 2013 Vol.25(1): 25-27